2013
DOI: 10.1002/chem.201300209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Rhenium‐Catalyzed Alcohol‐To‐Olefin Dehydration Reaction

Abstract: Rhenium-based complexes are powerful catalysts for the dehydration of various alcohols to the corresponding olefins. Here, we report on both experimental and theoretical (DFT) studies into the mechanism of the rhenium-catalyzed dehydration of alcohols to olefins in general, and the methyltrioxorhenium-catalyzed dehydration of 1-phenylethanol to styrene in particular. The experimental and theoretical studies are in good agreement, both showing the involvement of several proton transfers, and of a carbenium ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…One such reaction is deoxydehydration (DODH), in which a vicinal diol is transformed into an alkene in the presence of a reductant and a Re catalyst. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Multiple reductants and Re-based catalysts have been tested and, in particular, the CH 3 ReO 3 -catalyzed DODH driven by the oxidation of a secondary alcohol has received increasing attention over the past four years [10,11,17,19,20] and has recently been the topic of two reviews. [22,23] In this work, we present an in situ-spectroscopic investigation of a slightly modified version of this reaction (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…One such reaction is deoxydehydration (DODH), in which a vicinal diol is transformed into an alkene in the presence of a reductant and a Re catalyst. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Multiple reductants and Re-based catalysts have been tested and, in particular, the CH 3 ReO 3 -catalyzed DODH driven by the oxidation of a secondary alcohol has received increasing attention over the past four years [10,11,17,19,20] and has recently been the topic of two reviews. [22,23] In this work, we present an in situ-spectroscopic investigation of a slightly modified version of this reaction (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[11] It has been highlighted twice, [12,13] been the subtopic of two reviews, [14,15] and recently both the uncatalyzed and transition-metal-catalyzed DODH were treated in a book chapter; [16] within the past two years, more than ten papers dealing with mechanistic investigations [17][18][19] and the development of new rhenium-based catalysts, [20,21] reductants, [22,23] substrates, [24,25] and catalysts based on other elements [26][27][28] have been published, and we therefore think that the time has come for a dedicated Minireview. [11] It has been highlighted twice, [12,13] been the subtopic of two reviews, [14,15] and recently both the uncatalyzed and transition-metal-catalyzed DODH were treated in a book chapter; [16] within the past two years, more than ten papers dealing with mechanistic investigations [17][18][19] and the development of new rhenium-based catalysts, [20,21] reductants, [22,23] substrates, [24,25] and catalysts based on other elements [26][27][28] have been published, and we therefore think that the time has come for a dedicated Minireview.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the formation of ions, in particular anions, is unlikely in absence of any stabilizing agent. A kinetic and theoretical study of the mechanism of MTO-catalyzed alcohol dehydration was recently reported by Korstanje et al [23] They state that carbenium ion intermediates were found to be involved, however, formation of Re V was not discussed. A similar mechanism as proposed for deoxydehydration (DODH) reactions [24] appears to be doubtful, because starting from 1 the intermediate methyloxorhenium(V) diolate, which was found to be crucial for olefin extrusion, cannot be formed.…”
mentioning
confidence: 99%